The COMPASS RICH-1 MPGD based photon detector performance. Issue 1 (1st November 2022) - Agarwala, J; Alexeev, M; Azevedo, C D R; Bradamante, F; Bressan, A; Büchele, M; Chatterjee, C; Chiosso, M; Cicuttin, A; Ciliberti, P; Crespo, M L; D'Ago, D; et al.
Abstract : In 2016 we have upgraded the COMPASS RICH by novel gaseous photon detectors based on MPGD technology. Four new photon detectors, covering a total active area of 1.5 m 2, have been installed in order to cope with the challenging efficiency and stability requirements of the COMPASS physics programme. The new detector architecture consists in a hybrid MPGD combination: two layers of THGEMs, the first of which also acts as a reflective photocathode thanks to CsI coating, are coupled to a bulk Micromegas on a pad-segmented anode. These detectors are the first application in an experiment of MPGD-based single photon detectors. Presently, we are further developing the MPGD-based PDs to make them adequate for a setup at the future EIC collider. All aspects of the COMPASS RICH-1 Photon Detectors upgrade are presented: R&D, engineering, mass production, QA and performance; the on-going development for collider application is also presented.